Salivary myoepithelial cells: an addendum. (2nd November 2018) - Triantafyllou, Asterios; Mikkelsen, Lauge Hjorth; Gnepp, Douglas R.; Andreasen, Simon; Hunt, Jennifer L.; Devaney, Kenneth O.; Vander Poorten, Vincent; Rinaldo, Alessandra; Willems, Stefan M.; Ferlito, Alfio
ABSTRACT: Salivary myoepithelial cells bear particular appendages and are involved in processes that have received incomplete attention in previous reviews. Here, cilia on myoepithelial cells are reviewed as regards substructure, occurrence, detection (electron microscopy, double immunofluorescence together with confocal microscopy), and roles (sensory reception, evolutionary homology, paracrine interaction). Attention is drawn to regressive changes affecting those cells (e.g. accumulation of lipofuscin), possible alterations of their cytoskeleton, internalization of apoptotic bodies and haemosiderin, and role in salivary microcalcification. The ability of differentiated salivary myoepithelial cells to divide is re-examined, particularly its increase in chronic inflammation and under experimental conditions. Caution with regard to histogenetic models of salivary neoplasia is re-emphasized; methodological deficiencies and areas of controversy are outlined; and lines of future research are suggested.